LINKING PERCEIVED SOCIAL SUPPORT TO SOCIAL ENTREPRENEURIAL INTENTION: THE MEDIATING ROLE OF ATTITUDE BECOMING SOCIAL ENTREPRENEUR - Purbo Jadmiko (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract. The present study aims at identifying the social entrepreneurial intention among undergraduates students in Bung Hatta University context by using the theory of planned bahaviour as the research framework. A 10-questionnaire was responded by 150 studens of Bung Hatta University. The data were collected by purposive random sampling method. The questions measured perceived social support, attitude towards becoming a social entrepreneur, and social entrepreneurial intention. The result shows that attitude towards becoming a social entrepreneur full mediation between perceived social support to social entrepreneurial intention. Perceived social support and attitude towards becoming a social entrepreneur showed the positive significant relationship with social entrepreneurial intentions. This research study contributes to the social entrepreneurship literature by introductiong perceived social support and attitude towards becoming a social entrepreneur as antecedents that also explains social entrepreneurial intention formation. Keywords: Perceived social support, attitude towards becoming a social entreprenuer (ATB), social entrepreneurial intention, the theory of planned behaviour